Preventing infectious diseases for healthy ageing: The VITAL public-private partnership project. Issue 37 (18th August 2020) - Van Baarle, Debbie; Bollaerts, Kaatje; Del Giudice, Giuseppe; Lockhart, Stephen; Luxemburger, Christine; Postma, Maarten J.; Timen, Aura; Standaert, Baudouin; ,
Abstract: Prevention of infectious diseases through immunisation of the growing ageing adult population is essential to improve healthy ageing. However, many licenced and recommended vaccines for this age group show signs of waning of the protective effect due to declining immune responses (immuno-senescence) and decreasing vaccine uptake. Today's major challenge is to improve vaccine effectiveness and uptake and to deploy efficient vaccination strategies for this age group. The Vaccines and InfecTious diseases in the Ageing popuLation (VITAL) project, with partners from 17 academic & research groups and public institutes as well as seven industry collaborators, aims to address this challenge. The ambition is to provide evidence-based knowledge to local decision makers. Using a holistic and multidisciplinary approach and novel analytical methods, VITAL will provide tools that allow the development of targeted immunisation programs for ageing adults in European countries. The project is based on four pillars focussing on the assessment of the burden of vaccine-preventable diseases in ageing adults, the dissection of the mechanisms underlying immuno-senescence, the analysis of the clinical and economic public health impact of vaccination strategies and the development of educational resources for healthcare professionals. By the end of the project, a clear, detailed, and integrated program should be available for implementing a consistent, affordable, and sustainable vaccination strategy for ageing adults with regular evaluations of its impact over time.